Adaptation and performance evaluation of “Potchefstroom Koekoek” chicken breeds at farmer’s management practice in Debub Ari and Bena-Tsemay districts of South Omo Zone, Ethiopia - Gonta Gobena, Elias (Journal of Science and Development, 2020)
The performance evaluation and adaptation of Koekoek breeds was conducted at Debub Ari and Bena-Tsemay districts. 18 households were selected purposely from both district and training was given. 30 day old chicks and 18 hay-box brooders were provided for each household. The chickens were vaccinated for New Castle Disease, Gumboro, and Mareks. Chickens were supplied with commercial starter ration for the first 45 days and then locally available feeds. Mortality during the first two weeks was 21.67% and 5.22% after the first two weeks up to 45 days with the overall survival of 73.11%. The highest percentage of mortality was occurred during the first two weeks. The mortality due to disease was lowest. The average body weight of both male and female Koekoek chickens at the age of 20 weeks was 1.404 and 1.213 Kg, respectively. Koekoek chickens reached the age at first laying was 186.28 days. The average egg production potential of the breed was 154.17 eggs per year per hen with a relative egg weight of 47.078 gm. Thus, the breeds were highly preferred due to survival, adaptation, scavenging, disease resistance, egg production, adaptation similarity with local breeds under the existing farmers' condition. Therefore, there should be accessibility of Koekoek breeds, attention on household’s selection, and farmers should be trained for better management and scaling up of breeds to enhance the productivity and maximize the household’s income from the breeds.